Implications of American College of Cardiology/American Heart Association (ACC/AHA) Cholesterol Guidelines on Statin Underutilization for Prevention of Cardiovascular Disease in Diabetes Mellitus Among Several US Networks of Community Health Centers. Issue 7 (July 2017) - Akhabue, Ehimare; Rittner, Sarah S.; Carroll, Joseph E.; Crawford, Phillip M.; Dant, Lydia; Laws, Reesa; Leo, Michael C.; Puro, Jon; Persell, Stephen D.
Abstract : Background: Little is known about statin underutilization among diabetes mellitus patients cared for in community health centers, which tend to serve socioeconomically disadvantaged populations. Implications of the American College of Cardiology/American Heart Association (ACC/AHA) guidelines on preexisting gaps in statin treatment in this population are unclear. Methods and Results: We included 32 440 adults (45% male, 63% nonwhite, 29% uninsured/Medicaid) aged 40 to 75 years with diabetes mellitus who received care within 16 community health center groups in 11 states in the Community Health Applied Research Network during 2013. Statin prescribing was analyzed as a function of concordance with the National Cholesterol Education Program Adult Treatment Panel 2001 and ACC/AHA 2013 guidelines. More patients' treatments were concordant with the ACC/AHA (52.8%) versus the National Cholesterol Education Program Adult Treatment Panel (36.2%) guideline. Female sex was associated with lower concordance for both (odds ratio [OR] 0.90, CI 0.85‐0.94; and OR 0.84, CI 0.80‐0.88, respectively). Being insured, an Asian/Pacific Islander, or primarily Spanish speaking were associated with greater concordance for both guidelines: 35.5% (11 526/32 440) were concordant with neither guideline, the majority (79.7%) having no statin prescribed; 28.2% (9168/32 440) were concordant with ACC/AHA but not the National Cholesterol Education Program Adult Treatment Panel. 8.7% of these patients had a low‐density lipoprotein cholesterol >160 mg/dL despite having a moderate‐ or high‐intensity statin prescribed. And 11.6% (3772/32 440) were concordant with the National Cholesterol Education Program Adult Treatment Panel but not with ACC/AHA. Most of these patients had a low‐density lipoprotein cholesterol between 70 and 99 mg/dL with no or a low‐intensity statin prescribed. Conclusions: Opportunities exist to improve cholesterol management in diabetes mellitus patients in community health centers. Addressing care gaps could improve cardiovascular disease prevention in this high‐risk population.